Frictional force analysis of stent retriever devices using a realistic vascular model: Pilot study - Kwak, Youngseok; Son, Wonsoo; Kim, Byoung-Joon; Kim, Myungsoo; Yoon, Sang-Youl; Park, Jaechan; Lim, Jongkyeong; Kim, Joonwon; Kang, Dong-Hun (Frontiers in Neurology, 2022)
Objective To date, no vascular model to analyze frictional forces between stent retriever devices and vessel walls has been designed to be similar to the real human vasculature. We developed a novel in vitro intracranial cerebrovascular model and analyzed frictional forces of three stent retriever devices. Methods A vascular mold was created based on digital subtraction angiography of a patient's cerebral vessels. The vascular model was constructed using polydimethylsiloxane (PDMS, Dow Corning, Inc.) as a silicone elastomer. The vascular model was coated on its inner surface with a lubricating layer to create a low coefficient of friction (~0.037) to closely approximate the intima. A pulsatile blood pump was used to produce blood flow inside the model to approximate real vascular conditions. The frictional forces of Trevo XP, Solitaire 2, and Eric 4 were analyzed for initial and maximal friction retrieval forces using this vascular model. The total pulling energy generated during the 3 cm movement was also obtained. Results Results for initial retrieval force were as follows: Trevo, 0.09 ± 0.04 N; Solitaire, 0.25 ± 0.07 N; and Eric, 0.33 ± 0.21 N. Results for maximal retrieval force were as follows: Trevo, 0.36 ± 0.07 N; Solitaire, 0.54 ± 0.06 N; and Eric, 0.80 ± 0.13 N. Total pulling energy (N·cm) was 0.40 ± 0.10 in Trevo, 0.65 ± 0.10 in Solitaire, and 0.87 ± 0.14 in Eric, respectively. Conclusions Using a realistic vascular model, different stent retriever devices were shown to have statistically different frictional forces. Future studies using a realistic vascular model are warranted to assess SRT devices.